Conjugation with Acridines Turns Nuclear Localization Sequence into Highly Active Antimicrobial Peptide. (December 2015) - Zhang, Wei; Yang, Xiaoli; Song, Jingjing; Zheng, Xin; Chen, Jianbo; Ma, Panpan; Zhang, Bangzhi; Wang, Rui
ABSTRACT: The emergence of multidrug-resistant bacteria creates an urgent need for alternative antibiotics with new mechanisms of action. In this study, we synthesized a novel type of antimicrobial agent, Acr3 -NLS, by conjugating hydrophobic acridines to the N-terminus of a nuclear localization sequence (NLS), a short cationic peptide. To further improve the antimicrobial activity of our agent, dimeric (Acr3 -NLS)2 was simultaneously synthesized by joining two monomeric Acr3 -NLS together via a disulfide linker. Our results show that Acr3 -NLS and especially (Acr3 -NLS)2 display significant antimicrobial activity against gram-negative and gram-positive bacteria compared to that of the NLS. Subsequently, the results derived from the study on the mechanism of action demonstrate that Acr3 -NLS and (Acr3 -NLS)2 can kill bacteria by membrane disruption and DNA binding. The double targets–cell membrane and intracellular DNA–will reduce the risk of bacteria developing resistance to Acr3 -NLS and (Acr3 -NLS)2 . Overall, this study provides a novel strategy to design highly effective antimicrobial agents with a dual mode of action for infection treatment.